Statistics for solving environmental problems - Elfaki, Faiz Ahmed Mohamed; Hadi, Agung Efriyo; Usman, Mustofa (2013)
Mathematical models are now widely used in almost all scientific and engineering disciplines, including various important environmental applications, often describing dynamical systems. Focus on specific aspects typically reduces a complex system into a simpler one described by stochastic or deterministic variables, in a trade-off between simplicity and accuracy. Successful models of complex systems adequately represent key components and relevant interactions. Of models with roughly equal predictive power, the simplest one is the most desirable.